Assessment of suicidal tendencies among depressive patients in Psychiatric Hospital in Baghdad City - A. Hammo, Siham (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: To assess suicidal tendencies among depressive patients, to identify the significant differences of depressive patients with regard to their gender, age, level of education, occupational status, marital status, place of residence, income.Design: A descriptive analytical study starting from March to December 2016 such an assessment approach is applied to achieve the objectives of the studyMethodology: A purposive nonprobability sample of 73 depressed patients from outpatient clinic in Ibn Rushd Hospital and Medical city in Baghdad Al- Rusafa. The tool is constructed by relying on the construction of a questionnaire survey of global psychiatric Society (WPS), previous studies and related literature. A pilot study was carried out through the panel of experts and reliability of the questionnaire. Data was collected through a semi structured interview from 1\4\2016 to 30\4\2016. Data were analyzed through descriptive statistical data analysis approach (frequency, percentage and mean) and inferential statistical analysis (Cronbach alpha correlation coefficient and Chi- square test).Results: This study showed the level of suicidal tendencies in depressive patients and showed the statistical differences between some of demographic characteristics of patients with suicidal tendenciesConclusion: A moderate level of suicidal tendencies was observed among depressive patients, no (age, and level of education, marital status, residential area, and income) differences was noticed, gender and occupational status were affecting suicidal tendencies.Recommendation: Family intervention programs should be started by mental health nurses to provide a adequate information regarding the nature of major depressive disorder, the need for long treatment, and to identify the early signs of suicidal tendencies. Social and financial support for chronically depressive patients living in the community who cannot get family and self-support.